The development of students worksheet on immune system topic based on PBL - Rahmi, Yosi Laila; Andini, Yuni Fatma; Alberida, Heffi; Yogica, Relsas (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2023)
The immune system is a biological topic that is commonly discovered in daily life. This study aims to develop Problem Based Learning-based student worksheets on immune system material for SMA/MA that are valid and practical which is crucial to enhance student’s problem-solving skills. This type of research is development research, using 4D-Models. The instruments of this research are teacher interview sheet, validity test questionnaire sheet and practicality test questionnaire sheet. The worksheet was validated by two lecturers of the Department of Biology FMIPA UNP and one biology teacher of MAN 2 Padang City. Worksheet was tested on one biology teacher of MAN 2 Kota Padang and 36 students of class XII IPA 9 MAN 2 Kota Padang to test the practicality of the developed product. The object of research is Problem Based Learning based worksheet on immune system material for SMA/MA. The data used are data from the validity test and the practicality test. The data analysis technique is qualitative analysis for the define and design stages while quantitative analysis for the develop stage. Based on the research that has been done, the average validity value is 86.48% (valid). Practicality test of worksheet by teachers obtained results of 90.62% (very practical) and practicality test of worksheet by students obtained results of 94.31% (very practical). It can be concluded that the Problem Based Learning-based student worksheet on immune system material for SMA/MA developed is valid and very practical.